2023
DOI: 10.1039/d3se00122a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activated carbon lithium-ion capacitor electrochemical stability through electrolyte dielectric optimisation

Abstract: Interactions between electrolyte constituents and active materials strongly influence the capacity, energy density, and cycling stability of energy storage devices. In this study, the role of electrolyte dielectric on the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…While the upper cutoff limit of 4.2 V vs. Li/Li + is in good agreement with other studies, [15,47] the cathodic potential limit is lower than in other studies investigating 1 M LiPF 6 + EC/DMC on AC. Wohlfahrt-Mehrens et al identified the cathodic stability limit of YP-50 AC in 1 M LiPF 6 + EC/DMC (1 : 1) to be 1.5 V vs. Li/ Li + by voltammetric window opening experiments.…”
Section: Comparison To Electrochemical Stability Window Of Lipfsupporting
confidence: 91%
See 2 more Smart Citations
“…While the upper cutoff limit of 4.2 V vs. Li/Li + is in good agreement with other studies, [15,47] the cathodic potential limit is lower than in other studies investigating 1 M LiPF 6 + EC/DMC on AC. Wohlfahrt-Mehrens et al identified the cathodic stability limit of YP-50 AC in 1 M LiPF 6 + EC/DMC (1 : 1) to be 1.5 V vs. Li/ Li + by voltammetric window opening experiments.…”
Section: Comparison To Electrochemical Stability Window Of Lipfsupporting
confidence: 91%
“…À anion, deposition of carbonate due to EC decomposition, and formation of surface defects on the AC as degradation pathways. [15] In another study involving LIC full cells, the generation of HF acid at the AC cathode at a potential of 4.27 V vs. Li/Li + was found to result from oxidative decomposition of the PF 6…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Properties of the electrolytes, such as dielectric, viscosity, and conductivity, have also been demonstrated to affect the self-discharge, rate performance, and electrochemical stability of the AC cathode. Eleri et al [128] revealed that the electrolyte dielectric can influence the electrochemical stability of the AC cathode. Increasing the electrolyte dielectric improved the anion oxidative stability at the double layer region by modifying the solvation shell and increasing the resistance to oxidation during polarization at high energies.…”
Section: Electrolyte Dielectric and Viscositymentioning
confidence: 99%